A dark matter in sake brewing: Origin of microbes producing a Kimoto-style fermentation starter - Ito, Kohei; Niwa, Ryo; Kobayashi, Ken; Nakagawa, Tomoyuki; Hoshino, Genki; Tsuchida, Yuji (Frontiers in Microbiology, 2023)
In Kimoto-style fermentation, a fermentation starter is produced before the primary brewing process to stabilize fermentation. Nitrate-reducing bacteria, mainly derived from brewing water, produce nitrite, and lactic acid bacteria such as Leuconostoc can proliferate because of their tolerance towards low temperature and their low nutritional requirements. Later, Lactobacillus becomes the dominant genus, leading to weakly acidic conditions that contribute to control yeasts and undesired bacterial contaminants. However, the sources of these microorganisms that play a pivotal role in Sake brewing have not yet been revealed. Thus, comprehensive elucidation of the microbiome is necessary. In this study, we performed 16S rRNA amplicon sequencing analysis after sampling from floor, equipment surfaces, and raw materials for making fermentation starters, including koji, and water in Tsuchida Sake brewery, Gunma, Japan. Amplicon sequence variants (ASVs) between the external environments and the fermentation starter were compared, and it was verified that the microorganisms in the external environments, such as built environments, equipment surfaces, and raw materials in the sake brewery, were introduced into the fermentation starter. Furthermore, various adventitious microbes present in the fermentation starter of early days and from the external environments were detected in a nonnegligible proportion in the starter, which may impact the taste and flavor. These findings illuminate the uncharacterized microbial dark matter of sake brewing, the sources of microbes in Kimoto-style fermentation.